Professional Stress and Personality Traits as a Factor in Coping with Teachers´ Stress - Stanković-Đorđević, Mirjana M. (Collection of Papers of the Faculty of Philosophy in Priština, 2018)
In the framework of modern market economy, aside from various skills and knowledge, teachers are required to contrive a complex mosaic of roles and interactions which may result in the experience of prolonged stress and professional burnout. According to Lazarus and Folkman (2004), the manner of coping with the stress, as stated in their transaction model, implies a dynamic process which changes over time depending on objective requirements and subjective assessments of the situation for the purpose of solving the problem and/or reducing the intensity of a psychophysiological reaction within the stress process. Since the 1970s increasing importance has been attached to teachers´ experience of stress and the manner of coping with it. Kyriacou and Sutcliffe (1978) define teacher´s stress as a reaction to negative affects – anger, anxiety, tension, frustration, or depression, which result in potentially pathogenic physiological or biochemical changes. General factors of professional stress are present in all cultures and they are determined by the general status of education. Specific factors stem from a specific social environment, as well as from the professional status of teachers and their competences. Specific stress factors are related to the teacher´s personality, their value system in the process of interaction with the particular environment. Some of the significant personality traits, studied as specific factors of the professional stress, are dimensional models of personality within the five-factor model—self-efficiency, self-silencing, job satisfaction, styles of coping with stress, the level of burnout. According to research studies, the experience of professional stress and burnout is influenced by higher levels of neuroticism, aggressiveness, self-silencing, higher values of optimism, emotional competence, self-efficiency, life satisfaction, styles of coping with stress, as well as by the level of education at which teachers work. Research studies which the author has consulted mostly refer to teachers as a population at risk. Hence, aside from an analysis of professional stress factors, the author recommends that it would be essential to study and suggest possible directions of preventive actions in order to preserve and improve teachers´ mental and physical health. In the current social moment, it appears that it is most beneficial to observe individual personality of teachers from the standpoint of positive psychology and develop teachers´ individual resources for coping with professional stress.
Keywords: teachers; professional stress; stress factors; teacher's traits